Search for flavor-changing non-standard neutrino interactions by MINOS - Adamson, P; Barr, G; Bishai, M; Blake, A; Bock, G; Bogert, D; Cao, S; Cherdack, D; Childress, S; Coelho, J; Corwin, L; Cronin-Hennessy, D; et al. (2013)
We report new constraints on flavor-changing non-standard neutrino interactions from the MINOS experiment, in which neutrino versus antineutrino interactions can be distinguished on an event-by-event basis. We analyzed a combined set of beam neutrino and antineutrino data from the well-understood NuMI beam, and found no evidence for deviations from standard neutrino mixing. The observed energy spectra constrain the non-standard neutrino interactions parameter to the range -0.20<εμτ<0.07(90%C.L.). © 2013 American Physical Society.